2016
DOI: 10.1016/j.asjsur.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for laparoscopic colectomy in colorectal cancer at a new regional hospital

Abstract: Laparoscopic colectomy for colorectal cancer in a new regional hospital is feasible and safe. It does not need additional time for learning. Laparoscopic sigmoidectomy can be considered as the initial surgery for a trainee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…In a previous report, the surgeons' procedure time stabilized after the performance of 15 sigmoidectomy procedures as the primary operator [11]. Although the experience of the scope operator should be considered an important contributor to a meticulous laparoscopic surgery, the learning curve of the scope operator may plateau after a relatively small number of times assisting with sigmoidectomy or anterior resection (approximately 4 procedures).…”
Section: Discussionmentioning
confidence: 97%
“…In a previous report, the surgeons' procedure time stabilized after the performance of 15 sigmoidectomy procedures as the primary operator [11]. Although the experience of the scope operator should be considered an important contributor to a meticulous laparoscopic surgery, the learning curve of the scope operator may plateau after a relatively small number of times assisting with sigmoidectomy or anterior resection (approximately 4 procedures).…”
Section: Discussionmentioning
confidence: 97%
“…In the present trial, participation in at least 30 laparoscopic surgeries was required. Although it might be debatable as to whether 30 surgeries is an appropriate number, research into the learning curve in the first half of the 2000s, and also in recent reports, found that laparoscopic procedures stabilized when surgeons had experienced approximately 30 procedures . Certification by the endoscopic surgical skill qualification system introduced by JSES has been required since 2 years after the first patient was registered in this trial (2006) .…”
Section: Discussionmentioning
confidence: 99%
“…La courbe d’apprentissage ne doit pas constituer un frein à l’utilisation de la laparoscopie en particulier dans les cancers coliques non métastatiques. Une équipe asiatique a étudié l’impact de la courbe d’apprentissage dans un hôpital régional et a montré que cette voie d’abord était parfaitement sure et reproductible [23]. Dans notre série, la courbe d’apprentissage a eu un impact sur le temps opératoire sans pour autant influencer la morbi-mortalité, la récidive ou la survie.…”
Section: Discussionunclassified